Relationship Between Post Partum Mother's Knowledge About The Importance Of Colostrum And Mother's Interest In Giving Colostrum - Khofidhotur Rofiah; Betanuari Sabda Nirwana; Sutrisni; Alfika Awatiszahro; Erike Yunicha V (Universitas STRADA Indonesia, 2023)
The World Health Organization (WHO) shows that there are 170 million malnourished children worldwide. One of the effects is not to provide breast milk (breast milk) first, namely colostrum as initial immunity in children. A preliminary study at the Tiron Health Center in April 2023 found that only 10% of babies were breastfed after the first birth.This study wants to prove whether there is a relationship between postpartum maternal knowledge about the importance of colostrum with maternal interest in giving colostrum to infants This study is a relational analytical research using a cross sectional approach. The population in this study was 180 people with incidental sampling techniques. The variable measured is Post Partum Mother's Knowledge of the Importance of Colostrum as an independent variable, while the dependent variable is the mother's interest in giving colostrum to her baby.The results obtained from this study are that almost all (80%) maternity mothers have good knowledge and only a small percentage (10%) of mothers have sufficient knowledge and (10%) mothers have less knowledge about colostrum. The statistical test used in this study is the Spearman Rho test obtained calculation results with a significant value of ρ value = 0.000 while α = 0.05. Since the significant value is smaller than α = 0.05, H1 is accepted, thus There is a relationship between the mother's postpartum knowledge of the importance of colostrum and the mother's interest in giving colostrum to the baby.As a health teanaga who knows the importance of breastfeeding (breast milk) the first is colostrum. Let's make the 0-6 month breastfeeding program a success for babies, so that they can give birth to more qualified future generations.